2018
DOI: 10.1097/mph.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

An Infant With Unusually High Unconjugated Hyperbilirubinemia Due to Coexistence of Hereditary Spherocytosis and Gilbert Syndrome

Abstract: Hereditary spherocytosis is the most frequent congenital hemolytic anemia and is characterized with variable degree of anemia, jaundice, and splenomegaly. In the case of severe hyperbilirubinemia out of proportion with hemolysis, other causes of hyperbilirubinemia must be considered. Gilbert syndrome (GS) is an autosomal dominant disorder characterized with intermittent hyperbilirubinemia without any other sign and symptom of liver disease as a result of reduced activity of uridine diphosphate-glucuronyl trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Hereditary spherocytosis (HS) is a kind of hemolytic anemia with jaundice, hemolysis, and splenomegaly (Butorac et al, 2018; He et al, 2018) as the main clinical features, caused by changes in the structure of red blood cell membrane proteins. This disease occurs all over the world, with different incidences in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary spherocytosis (HS) is a kind of hemolytic anemia with jaundice, hemolysis, and splenomegaly (Butorac et al, 2018; He et al, 2018) as the main clinical features, caused by changes in the structure of red blood cell membrane proteins. This disease occurs all over the world, with different incidences in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…The reports were summarized in Table II for UGT1A1 genetic mutations and related diseases during the past 4 years. Butorac et al (7) reported the coexistence of hereditary spherocytosis and GS in a 21-month-old girl with unconjugated hyperbilirubinemia. Li et al (20) reported the combination of myeloproliferative neoplasms and the presence of the insertion mutation with the (TA)6TAA box and the missense mutation (G→A) at 211 bp of exon 1 in the UGT1A1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Several variations in the UGT1A1 gene have been described, including UGT1A1*28, UGT1A1*60 and UGT1A1*93 (3,4). GS in combination with diseases, such as thalassemia, glucose-6 -phosphate dehydrogenase (G6PD) deficiency, spherocytosis and acute lymphoblastic leukemia may potentiate severe hyperbilirubinemia (5)(6)(7)(8)(9). In addition, GS may decrease plasma oxidation and affect drug metabolism, such as irinotecan hydrochloride by decreasing the ability to conjugate drugs (10).…”
Section: Introductionmentioning
confidence: 99%
“…2 The calculated rate of coexistence of GS and HS is 15 to 35/million births. 3 Herein, we present a case with jaundice of unknown cause and finally diagnosed as HS combined with GS by the laboratory test results, imaging findings, and the results of liver pathological examination and exome sequencing.…”
Section: Introductionmentioning
confidence: 99%